Pengaruh Kualitas Sumber Daya Aparatur Sipil Negara Terhadap Sikap Kerja Pegawai di Badan Meteorologi Klimatologi dan Geofisika Provinsi Sulawesi Utara - Saragih, Elfridawati; Mingkid, Elfie; Rumawas, Wehelmina (JURNAL ILMIAH SOCIETY, 2016)
The purpose of this study is to analyze and explain the magnitude of the effect of the quality of the resources of the State Civil Administrative work attitude of employees in Meteorology and Geophysics North Sulawesi province. This research is a quantitative research survey explanatory research design. The results of this study indicate that the physical quality and health Apparatus State Civil partially have an influence on the work attitude of employees, knowledge and skills partially have influence on work attitudes Spiritual and kejuangan partially have an influence on the attitude of employees working at the Meteorology and Geophysics Sulawesi North. Physical Quality and Health, Knowledge and Skills, as well as Spiritual and Kejuangan simultaneously have an influence on employee attitudes. Among the three independent variables variables that most influence on the attitudes of employees working at the Meteorology and Geophysics North Sulawesi province is the spiritual and kejuangan. Keywords: Quality, Work Attitude